TOPOLINO vs MICKEY MOUSE – AN UNEVEN MATCH: SOME REMARKS ON THE CROSS-CULTURAL RECEPTION OF COMICS - Ochse, Elana (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2018)
Known as Mickey Mouse in English, Topolino has been so relevant to Italians, both young and old, that one of the most popular Fiat car models back in the 1950s, a shaping status symbol for the upcoming post-war bourgeoisie, was named after him. The icon developed an aesthetic, from cartoons to films to advertising, which rapidly annihilated age, gender and class boundaries, with a bit of frowning from conservative teachers. Foreigners, however, are astonished to discover that Topolino is not just tolerated but welcomed in most Italian homes – thoroughly nationalised and largely naturalised. The difference lies in the verbal dimension, which in the English-speaking world is not appreciated by most adults. Why do intellectual, and even elitist Italian adults perceive the creature as simpatico, and why instead do educated Brits and Americans tend to consider his language as a model which you would not want your child to grow up with? There are national discourses of education impacting not so much on the reception of the semiotics of cartoons, nor on their proposed political/social models but on lexically, syntactically and above all “socially inappropriate” language use. This resistant Gordian knot tying up the “doing” of class with discourses of parenting, education and language pragmatics will be undone in this paper by showing how the Italian Topolino, analysed in a translation class, reveals a degree of linguistic sophistication/creativity unknown in the English genre and text-type.